Comparison of different cereal grains for hydroponic fodder production in locally constructed polyhouse at Khumaltar, Lalitpur, Nepal - Upreti, Sujaya; Ghimire , Ram P.; Banskota, Niraj (Journal of Agriculture and Natural Resources, 2022)
Hydroponic fodder production technology involves an intensive method of quality fodder production in less space and in a shorter duration. An experiment was conducted to compare the different cereal grains under hydroponic fodder production for the fodder yield, fodder quality, and per unit production cost in a locally constructed polyhouse. Maize (Zea mays L.), oat (Avena sativa L.) and wheat (Triticum aestivum L.) were evaluated as the treatments. The experiment was carried out in Completely Randomized Design (CRD) with 12 replications at National Pasture and Fodder Research Program in July 2017 and July 2018. The observations were taken on plant morphological characters, fodder yield (including root mat), fodder nutrient composition and expenses in variable costs. The results of the study showed that the fodder yield varied significantly (P<0.05) for different cereal grains. The hydroponic fodder yields from each kg grain were recorded higher in fodder oat (7.96 kg) compared to wheat (6.76 kg) and maize (5.32 kg). Similarly, the crude protein (CP) content of the fodder was higher in wheat (16.16%) compared to oat (13.96%) and maize (12.51%). The cost of hydroponic maize, oat and wheat fodder production were obtained as recorded NPR 20.64, 24.67 and 18.76 per kg, respectively.